2015
DOI: 10.18632/aging.100720
|View full text |Cite
|
Sign up to set email alerts
|

Aging-dependent alterations in gene expression and a mitochondrial signature of responsiveness to human influenza vaccination

Abstract: To elucidate gene expression pathways underlying age-associated impairment in influenza vaccine response, we screened young (age 21-30) and older (age ≥65) adults receiving influenza vaccine in two consecutive seasons and identified those with strong or absent response to vaccine, including a subset of older adults meeting criteria for frailty. PBMCs obtained prior to vaccination (Day 0) and at day 2 or 4, day 7 and day 28 post-vaccine were subjected to gene expression microarray analysis. We defined a respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 37 publications
5
82
0
2
Order By: Relevance
“…2A). Interestingly, the abnormally expanded "superlineages" continued to make up a similar fraction of the total repertoire at days 7 and 28 after vaccination as they did before vaccination at day 0, indicating that the size of any vaccine response [e.g., release of recalled IgG plasmablasts around day 7 (11,24,25)] was minor compared with the weight of the superlineages. Note that no CDR3 sequences were shared between superlineages, which provides confidence that superlineages did not arise from contamination.…”
Section: Resultsmentioning
confidence: 96%
“…2A). Interestingly, the abnormally expanded "superlineages" continued to make up a similar fraction of the total repertoire at days 7 and 28 after vaccination as they did before vaccination at day 0, indicating that the size of any vaccine response [e.g., release of recalled IgG plasmablasts around day 7 (11,24,25)] was minor compared with the weight of the superlineages. Note that no CDR3 sequences were shared between superlineages, which provides confidence that superlineages did not arise from contamination.…”
Section: Resultsmentioning
confidence: 96%
“…2A) and the previously published observation that both the antibody and transcriptional responses to vaccination have strong age dependencies (5, 26), we opted to divide each of the cohorts into young (35 years and below) and older (60 years and above) groups and analyzed them separately. This approach allowed us to uncover signatures beyond those driven by age, which was the focus of the original studies, as well as other existing studies (3, 5, 14). It allowed us to compare response signatures in young versus older adult participants, which is an important issue that has been largely unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…Last, it is well-known that experimental measurements are subject to batch effects (33), and failure to account for these differences may hinder comparisons across studies. Although multiple studies have suggested postvaccination transcriptional signatures that are associated with titer responses to influenza vaccination (5, 12, 15, 34, 35), only a few have identified baseline signatures that are significantly associated with the antibody response (3, 7, 13, 14), and none of these baseline signatures were found and then further validated using independent cohorts. Furman et al (14) analyzed a cohort of 91 individuals (SDY212) and identified an age- and apoptosis-related gene module that was correlated with the hemagglutination inhibition assay (HAI) response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schoggins-gene-set defines Interferon Stimulated Genes (ISGs) and has been reported to be significantly enriched upon influenza infections by previous studies [8, 23]. 43 out of 50 FCM-gene-sets were found enriched in at least one of the pathways ( p value <0.01) (Fig.…”
Section: Resultsmentioning
confidence: 89%